Technology transfer and valuation methods in use by university technology transfer offices - Rocha, António Miguel Sousa (2023)
Valuing research deliverables implies the assessment of knowledge, skills, and solutions that can create benefits for a wide scope of stakeholders, including researchers, research units, universities, businesses, and the larger society. Investing in early-stage technology or technology that is novel and has an inventive step can imply a high-risk investment. High-quality information and advice are needed, and valuation methods are required, to support decision making regarding intellectual property rights protection, define a technology value proposition, devise a roadmap to bring technology into the market, and support negotiations with potential licensees. To provide information and evidence regarding the main technology valuation methods in use by Portuguese University Technology Transfer Offices (TTOs), qualitative and quantitative data have been collected by surveying and interviewing eight Portuguese University TTOs. From the data it was possible to conclude that pre-defined rating/ranking methods and models are the most frequently used valuation methods, followed by market valuation approaches. Previous agreements and discounted cash-flow projections are mainly used when a spin-off firm is under consideration or when there is a manifestation of interest from a potential investor. Royalty standards are used to prepare licensing negotiations, and Real Options, Monte Carlo simulation, rules of thumb, and Auctions are not being used.